2022
DOI: 10.1039/d1tb02273c
|View full text |Cite
|
Sign up to set email alerts
|

A natural polysaccharide-based antibacterial functionalization strategy for liquid and air filtration membranes

Abstract: A natural polysaccharide-based strategy was developed for the facile and universal antimicrobial functionalization of filtration materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Compared to synthetic electrets, naturally charged polymers are most promising for long-lasting air filtration, as they can achieve high electrostatic adsorption without recharging and regeneration. Chitosan is a charged natural polymer with promise for long-lasting air filtration. Chitosan comprises N -acetyl- d -glucosamine and β-(1–4)-linked d -glucosamine with a highly stable distribution of naturally positively charged groups on its backbone. The ionizable amino and hydroxyl groups of chitosan facilitate the binding of negatively charged particles in the air and can improve the filtration efficiency of chitosan-based filters. Moreover, the positive charge of chitosan interacts with the envelope proteins of viruses, disrupts viruses’ structure, or interferes with their replication. For example, Hathout and Kassem suggested that the application of positively charged chitosan or poly- l -lysine fibers in personal protective masks or protective clothing could reduce the viral load by exploiting the electrostatic repulsion between the fibers and SARS-CoV-2 (Figure c) .…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%
“…Compared to synthetic electrets, naturally charged polymers are most promising for long-lasting air filtration, as they can achieve high electrostatic adsorption without recharging and regeneration. Chitosan is a charged natural polymer with promise for long-lasting air filtration. Chitosan comprises N -acetyl- d -glucosamine and β-(1–4)-linked d -glucosamine with a highly stable distribution of naturally positively charged groups on its backbone. The ionizable amino and hydroxyl groups of chitosan facilitate the binding of negatively charged particles in the air and can improve the filtration efficiency of chitosan-based filters. Moreover, the positive charge of chitosan interacts with the envelope proteins of viruses, disrupts viruses’ structure, or interferes with their replication. For example, Hathout and Kassem suggested that the application of positively charged chitosan or poly- l -lysine fibers in personal protective masks or protective clothing could reduce the viral load by exploiting the electrostatic repulsion between the fibers and SARS-CoV-2 (Figure c) .…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%
“…In this case, combining filtration functions with pathogen inactivation features would be a desirable solution to improve water disinfection effectiveness. 10,11 Given the robust rechargeable biocidal activity of Nhalamine structures against a broad spectrum of pathogens, many reports have informed of the usage of such structure in rapid and long-term antibacterial applications including water disinfection, 12−14 food preservation, 15−17 and medical personal protection. 18−20 N-halamine structures include imides, amides, and amines, which biocidal efficiency follows the trend of imide < amide < amine, while their active chlorine stabilities are in a reverse order (i.e., imide > amide > amine).…”
Section: Introductionmentioning
confidence: 99%
“…The former could effectively inactivate pathogens in water, but the function is irreversible and could cause secondary pollution due to the generation of toxic byproducts from the disinfectants, which are difficult to be removed from the water streams. , On the other hand, the emergence of various novel membranes could filtrate any pathogens in water mainly by a size-exclusive mechanism. , However, no pathogen inactivation function could be provided by such membranes, which poses high risks of cross-contamination. In this case, combining filtration functions with pathogen inactivation features would be a desirable solution to improve water disinfection effectiveness. , …”
Section: Introductionmentioning
confidence: 99%
“…To synchronously obtain high optical transparency and antibacterial property, the antibacterial agent should have excellent bactericidal action and comparable refractive index to PS. Polyhexamethylene guanidine (PHMG) is lethal to most bacteria, and the effect takes quickly, [13][14][15][16] which shows a promising potential in water purification, 17 air filtration, 18 and equipment. [19][20][21] The organic PHMG can be rapidly adsorbed to the negatively charged bacterial cell surface.…”
Section: Introductionmentioning
confidence: 99%